Clinical Impact and Safety of Anticoagulants for Portal Vein Thrombosis in Cirrhosis. (February 2019) - Pettinari, I.; Vukotic, R.; Stefanescu, H.; Pecorelli, A.; Morelli, Mc; Grigoras, C.; Sparchez, Z.; Andreone, P.; Piscaglia, F.
Abstract : Objectives: Portal vein thrombosis (PVT) is a frequent complication of cirrhosis. Benefit, safety, and duration of anticoagulant treatment in this setting are controversial issues. The aim of this study was to analyze the course of PVT in a large cohort of cirrhotic patients undergoing or not anticoagulation therapy. Methods: The data of 182 patients who presented between January 2008 and March 2016 with cirrhosis and PVT with at least 3 months of follow-up after the first PVT detection were analyzed. Eighty-one patients received anticoagulants and 101 were untreated per physician discretion. Results: The extension of the thrombosis decreased by >50% in 46 (56.8%, with complete recanalization in 31/46) patients under anticoagulation and in 26 (25.7%) untreated patients. Of the 46 patients who underwent recanalization, 17 (36%) suffered recurrent thrombosis after stopping anticoagulation therapy. Kaplan–Meier analysis showed a higher survival rate in the treated group ( p = 0.010). At multivariate analysis, anticoagulation was an independent factor associated with longer survival (HR:0.30, CI:0.10–0.91, p = 0.014). The Child–Turcotte–Pugh classes B/C negatively influenced survival (hazard ratio, (HR):3.09, confidence interval (CI):1.14–8.36, p = 0.027 for Child–Turcotte–Pugh B and HR:9.27, CI:2.67–32.23, p < 0.001 for Child–Turcotte–Pugh C). Bleeding complications occurred in 22 (21.8%) untreated and 16 (19.7%) treated patients, but in only four cases was it judged to be related to the anticoagulant treatment. No death was reported as a consequence of the bleeding events. Conclusions: Anticoagulant treatment is a safe and effective treatment leading to partial or complete recanalization of the portal venous system in 56.8% of cases, improving the survival of patients with cirrhosis and PVT. Discontinuation of the therapy is associated with a high rate of PVT recurrence.